2015
DOI: 10.1016/j.pbb.2015.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of age-associated cognitive deficits is accompanied by increased plasticity-related gene expression after chronic antidepressant administration in middle-aged mice

Abstract: Cognitive decline occurs during healthy aging, even in middle-aged subjects, via mechanisms that could include reduced stem cell proliferation, changed growth factor expression and/or reduced expression of synaptic plasticity genes. Although antidepressants alter these mechanisms in young rodents, their effects in older animals are unclear. In middle-aged mice, we examined the effects of a selective serotonin reuptake inhibitor (fluoxetine) and a multimodal antidepressant (vortioxetine) on cognitive and affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 140 publications
5
59
1
Order By: Relevance
“…Generally, locomotion decreases with advancing age in humans [84]; however, animal studies have reported inconsistent results regarding the age-related changes in the locomotor behavior. For example, some studies have demonstrated age-related decline in locomotor activity in WT mice [8587], while others have reported no significant age-related changes in locomotion [88, 89]. We found a significant increase in locomotion in the control LFD mice at 32 weeks compared to the 21 week time point, but our mice were not aged as the mice in [8587].…”
Section: Discussioncontrasting
confidence: 56%
“…Generally, locomotion decreases with advancing age in humans [84]; however, animal studies have reported inconsistent results regarding the age-related changes in the locomotor behavior. For example, some studies have demonstrated age-related decline in locomotor activity in WT mice [8587], while others have reported no significant age-related changes in locomotion [88, 89]. We found a significant increase in locomotion in the control LFD mice at 32 weeks compared to the 21 week time point, but our mice were not aged as the mice in [8587].…”
Section: Discussioncontrasting
confidence: 56%
“…Evidence from clinical trials suggests that vortioxetine ameliorates some aspects of MDD-associated cognitive impairment, for example, speed of processing, executive function, and memory. This is supported by evidence from a number of preclinical experiments (du Jardin et al, 2014; Jensen et al, 2014; Wallace et al, 2014; Li et al, 2015). Much of the recent research efforts from our laboratory have been aimed at understanding the biologic mechanism by which vortioxetine exerts these beneficial effects on cognitive function.…”
Section: Introductionmentioning
confidence: 70%
“…Therefore, if vortioxetine’s cholinergic mechanisms are mediated via effects at either of these targets, then our study may have underestimated the impact of the cholinergic system in clinical populations. Additionally, the behavioral data are limited to assessments of social recognition memory, object recognition memory, and attention; thus, caution should be exercised when extrapolating to other cognitive domains that are improved by vortioxetine in the clinic, for example, processing speed and executive function (du Jardin et al, 2014; Jensen et al, 2014; Wallace et al, 2014; Li et al, 2015). Moreover, although the neurochemical data presented in this work may suggest that vortioxetine has limited effects on cholinergic neurotransmission, this should be viewed with caution until empirical evaluations of other cognitive domains have been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, citalopram (up to 10 mg/kg) given sub-acutely to middle-aged OVX rats had no effect in the FST (Vega Rivera et al, 2016), although it did produce an AD-like effect in middle-aged OVX rats that had been subjected to chronic mild stress (Romano-Torres and Fernandez-Guasti, 2010). Chronic treatment with fluoxetine had no effect in middle-aged female mice (Li et al, 2015). …”
Section: Discussionmentioning
confidence: 99%